2022
DOI: 10.1177/07342829221096916
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and L2 Achievement: The Mediating Roles of Motivation and Self-Regulated Learning Among Iranian High School Students

Abstract: The current study investigated how perfectionism can be related to L2 learners’ achievement with motivation and two aspects of self-regulated learning as possible mediators. This study also evaluated the factor structure of the Big Three Perfectionism Scale (BTPS) in an Iranian sample. The participants were 495 Iranian high school students who completed six BTPS sub-scales and measures of self-determined motivation and self-regulated learning. Psychometric analyses indicated that rigid perfectionism and self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Also, higher scores in perfectionism were associated with higher scores in trait anxiety, suggesting that more perfectionist students would experience higher levels of trait anxiety. Chasetareh et al (2023) investigated the relationship between perfectionism and EFL learners' achievement, considering motivation and self-regulated learning as possible mediators. Their findings revealed that "higher levels of rigid perfectionism were positively related to deep learning and persistence that, in turn, were related to higher L2 achievement. "…”
Section: Writing Anxiety and Writing Performancementioning
confidence: 99%
“…Also, higher scores in perfectionism were associated with higher scores in trait anxiety, suggesting that more perfectionist students would experience higher levels of trait anxiety. Chasetareh et al (2023) investigated the relationship between perfectionism and EFL learners' achievement, considering motivation and self-regulated learning as possible mediators. Their findings revealed that "higher levels of rigid perfectionism were positively related to deep learning and persistence that, in turn, were related to higher L2 achievement. "…”
Section: Writing Anxiety and Writing Performancementioning
confidence: 99%
“…Persistence and the use of deep learning strategies is clearly advantageous to learning, and has been articulated as such in various perfectionism studies (e.g. Chasetareh et al, 2023 ; Mills & Blankstein, 2000 ; Vogel et al, 2019 ). However, this study indicates that the learning process is painfully slow, necessitates huge personal costs, and robs perfectionists of any gratification to be gained.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers concluded that we are better able to comprehend the L2 listening process thanks to the patterns of interaction between perfectionism and the two listening subprocesses. Chasetareh et al (2022) examined the relationship between perfectionism and L2 learners' accomplishment, looking at motivation and two components of self-regulated learning as potential mediators. The Big Three Perfectionism Scale (BTPS) factor structure was also assessed in this study using an Iranian population.…”
Section: Experimental Studiesmentioning
confidence: 99%